Early Clinical and Radiographic Results of Minimally Invasive Anterior Approach Hip Arthroplasty - Tamara Alexandrov; Elke R. Ahlmann; Lawrence R. Menendez (Advances in Orthopedics)
We present a retrospective review of the early results and complications in a series of 35 consecutive patients with 43 total hip arthroplasties performed through an anterior muscle sparing minimally invasive approach. We found the early complication rates and radiographic outcomes comparable to those reported from arthroplasties performed via traditional approaches. Complications included dislocation (2%), femur fracture (2%), greater trochanteric fracture (12%), postoperative periprosthetic intertrochanteric fracture (2%), femoral nerve palsy (5%), hematoma (2%), and postoperative iliopsoas avulsion (2%). Radiographic analysis revealed average cup anteversion of 19.6°±6.6, average cup abduction angle of 48.4°±7, stem varus of 0.9°±2, and a mean leg length discrepancy of 0.7 mm. The anterior approach to the hip is an attractive alternative to the more traditional approaches. Acceptable component placement with comparable complication rates is possible using a muscle sparing technique which may lead to faster overall recovery.